2007
DOI: 10.2166/wst.2007.240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hybrid processes for nitrification by comparing MBBR/AS and IFAS configurations

Abstract: An integrated fixed-film activated sludge (IFAS) pilot plant and a moving bed biofilm reactor coupled with an activated sludge process (MBBR/AS) were operated under different temperatures, carbon loadings and solids retention times (SRTs). These two types of hybrid systems were compared, focusing on the nitrification capacity and the nitrifiers population of the media and suspended biomass alongside other process performances such as carbonaceous and total nitrogen (TN) removal rates. At high temperatures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 6 publications
(6 reference statements)
0
23
0
1
Order By: Relevance
“…Researchers confirmed the improvement of nitrification at low temperatures in the presence of heterotrophic bacteria, because they act as a protective layer for the nitrifying bacteria. Nevertheless, in this situation, the specific activity of AOB is lesser than when only nitrifying bacteria are present (Germain et al 2007;Wu et al 2008). …”
Section: Nhmentioning
confidence: 93%
See 2 more Smart Citations
“…Researchers confirmed the improvement of nitrification at low temperatures in the presence of heterotrophic bacteria, because they act as a protective layer for the nitrifying bacteria. Nevertheless, in this situation, the specific activity of AOB is lesser than when only nitrifying bacteria are present (Germain et al 2007;Wu et al 2008). …”
Section: Nhmentioning
confidence: 93%
“…The addition had a marginal effect on the nitrification rate. pH and DO were automatically kept within the range of 7.6 ± 0.3 and C3 mg L -1 for both groups of bacteria (heterotrophic and autotrophic bacteria, respectively) (Gerardi 2002;Wu et al 2008). An MLSS concentration of 2 g L -1 was maintained throughout the experiment with mixed liquor purged from the reactors, and the centrifuged biomass of effluent was returned to the reactors.…”
Section: Nhmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, attached growth systems are generally considered less sensitive to toxic influents and variations in environmental conditions (Wang et al 2005). Several studies have demonstrated that, with MB, it is possible to get efficiencies in biochemical oxygen demand (BOD 5 ) greater than 90 % and greater than 85 % in chemical oxygen demand (COD) (Germain et al 2007;Davis et al 2009;Kim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Varios estudios indican que las plantas en las que se ha incluido MBBR IFAS consiguen un comportamiento general mejor que los fangos activos convencionales (Rusten et al 2003) (Germain et al 2007) (Di Trapani et al 2011). …”
Section: A) Nitrificaciónunclassified